Alpacas Shepherds - Flores Ochoa, Jorge A. (1975)
We try to make a summary of the alpaca herding societies of the Andean puna, showing characteristic aspects of their culture and social organization. The ethnographic summary that we present has been carried out, basically, with data obtained by the author and other people dedicated to the study of the society and culture of the shepherds in southern Peru, mainly in the departments of Cuzco and Puno. It is known that the grazing area extends to other departments, but information is still lacking. There are likely to be variations with what is described and the grazing of Ayacucho, Apurímac, Arequipa, Moquegua, Tacna, Lima, Cerro de Pasco.